Effect of sex and final fattening on ultrasound and carcass traits in Iberian pigs. - Ayuso, D; González, a; Hernández, F; Peña, F; Izquierdo, M (Meat science, 2014)
A hundred and twenty-five castrated Iberian pigs (61 males and 64 females, from 106.9 kg of live weight at star to 160.3 kg at slaughter) was used to investigate the effect of feeding system on carcass attributes (backfat thickness and loin area measured with ultrasound before slaughter, and intramuscular fat and weights and yields of hams, forelegs and loins after slaughter). Pigs were fattened outdoor under extensive conditions. There were 4 treatments: "montanera", M; "recebo", R; "cebo a campo", C; and high oleic fed, O). Ultrasound images were collected at two rib locations (10th and 14th). M and O groups had the highest fat thickness and loin area was lower in M than in C group. M and O showed higher carcass weight and yield than the other groups. The largest ham weight was for C and the lowest for M groups. Loin weight and yield were higher in M and R than the other two groups (O and C).
Keywords: Adipose Tissue; Adipose Tissue: chemistry; Adipose Tissue: ultrasonography; Animal Feed; Animal Feed: analysis; Animals; Body Weight; fatty acids; Fatty Acids: analysis; Female; Image Processing, Computer-Assisted; Male; meat; Meat: analysis; Muscle, Skeletal; Muscle, Skeletal: chemistry; Muscle, Skeletal: ultrasonography; Phenotype; Sex Factors; Swine

Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro; Olivares, Álvaro (Archives of Animal Nutrition, 2006)
Abstract This experiment was carried out to study the influence of age at the beginning of the free-range fattening period (traditional pigs, TP, age 12 months vs. young pigs, YP, age 8 months) on the performance of Iberian pigs. During 152 days prior to the fattening period, TP and YP pigs received 1.7 and 2.6 kg feed per day, respectively. During fattening, TP pigs had a higher average daily gain (p < 0.05) than YP pigs. The proportions of PUFA and n-3 fatty acids of the outer and inner layers of subcutaneous backfat were higher in TP than in YP pigs (p < 0.05), while the proportions of C16:0 and SFA in the inner layer of subcutaneous backfat were greater in YP than in TP pigs (p < 0.05). The ratio of n-6/n-3 in subcutaneous backfat was lower in TP than in YP pigs (p < 0.05). The percentage of intramuscular fat in longissimus dorsi muscle was higher in TP than in YP pigs (p < 0.05). The relationship between the percentage of intramuscular fat in longissimus dorsi muscle and average daily gain during the free-range fattening period adjusted to a quadratic function (p < 0.05). The concentration of α- and ?-tocopherol in subcutaneous backfat at slaughter was significantly higher in TP than in YP pigs (p < 0.05). It is concluded that Iberian pigs that have 8 months of age at the beginning of free-range feeding have adequate commercial quality.
From Duplicate 2 (Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro)
Keywords: a and g tocopherols; Adipose Tissue; Adipose Tissue: metabolism; Age Factors; alpha-Tocopherol; alpha-Tocopherol: analysis; Animal Feed; Animal Nutritional Physiological Phenomena; Animals; Body Composition; Body Composition: physiology; carcass quality; fatty acid proﬁle; fatty acids; Fatty Acids: analysis; free-range fattening; gamma-Tocopherol; gamma-Tocopherol: analysis; Growth; Male; Muscle; Pig age; Skeletal; Skeletal: anatomy & histology; Skeletal: chemistry; Swine; Swine: growth & development; Weight Gain

Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro; Olivares, Álvaro (Archives of Animal Nutrition, 2006)
Abstract This experiment was carried out to study the influence of age at the beginning of the free-range fattening period (traditional pigs, TP, age 12 months vs. young pigs, YP, age 8 months) on the performance of Iberian pigs. During 152 days prior to the fattening period, TP and YP pigs received 1.7 and 2.6 kg feed per day, respectively. During fattening, TP pigs had a higher average daily gain (p < 0.05) than YP pigs. The proportions of PUFA and n-3 fatty acids of the outer and inner layers of subcutaneous backfat were higher in TP than in YP pigs (p < 0.05), while the proportions of C16:0 and SFA in the inner layer of subcutaneous backfat were greater in YP than in TP pigs (p < 0.05). The ratio of n-6/n-3 in subcutaneous backfat was lower in TP than in YP pigs (p < 0.05). The percentage of intramuscular fat in longissimus dorsi muscle was higher in TP than in YP pigs (p < 0.05). The relationship between the percentage of intramuscular fat in longissimus dorsi muscle and average daily gain during the free-range fattening period adjusted to a quadratic function (p < 0.05). The concentration of α- and ?-tocopherol in subcutaneous backfat at slaughter was significantly higher in TP than in YP pigs (p < 0.05). It is concluded that Iberian pigs that have 8 months of age at the beginning of free-range feeding have adequate commercial quality.
From Duplicate 2 (Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro)From Duplicate 2 (Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro)The following values have no corresponding Zotero field: publisher: Taylor & Francis accession-num: 16921928
Keywords: a and g tocopherols; Adipose Tissue; Adipose Tissue: metabolism; Age Factors; alpha-Tocopherol; alpha-Tocopherol: analysis; Animal Feed; Animal Nutritional Physiological Phenomena; Animals; Body Composition; Body Composition: physiology; carcass quality; fatty acid proﬁle; fatty acids; Fatty Acids: analysis; free-range fattening; gamma-Tocopherol; gamma-Tocopherol: analysis; Growth; Male; Muscle; Pig age; Skeletal; Skeletal: anatomy & histology; Skeletal: chemistry; Swine; Swine: growth & development; Weight Gain

Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila (Journal of Agricultural and Food Chemistry, 2003)
The gastroprotective effects of 70% acetone extracts of Quercus suber and Quercus coccifera leaves and of tannins (pedunculagin, castalagin, phillyraeoidin A, and acutissimin B) purified from these extracts were examined in the mouse using the ethanol-induced gastric ulcer model. Both extracts (25, 50, and 100 mg/kg), given orally, prevented the formation of ethanol-induced lesions in the stomach. The percent protection varied between 68 and 91%. Purified tannins (50 mg/kg) were also effective in protecting the stomach against ethanol, and the percent protection varied from 66 to 83%. Castalagin was the most potent. Both extracts and all of the tannins tested (10, 25, and 50 ?g/mL) strongly inhibited (55?65%) the lipid peroxidation of rabbit brain homogenate. These results suggest that the gastroprotective effects of extracts of Q. suber and Q. coccifera leaves and the purified tannins in this experimental model are related to their anti-lipoperoxidant properties. Keywords: Experimental gastric ulcer; lipid peroxidation; medicinal plants; Quercus sp.; tannins; castalagin
From Duplicate 2 (Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila)
Keywords: Acetone; Animals; Biphenyl Compounds; castalagin; Catechols; Catechols: therapeutic use; Ethanol; Experimental gastric ulcer; Hydrolyzable Tannins; lipid peroxidation; Lipid Peroxidation: drug effects; Male; Medicinal plants; Mice; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: therapeutic use; Plant Leaves; Plant Leaves: chemistry; Quercus; Quercus sp.; Quercus: chemistry; Rabbits; Stomach Ulcer; Stomach Ulcer: chemically induced; Stomach Ulcer: prevention & control; Tannins; Tannins: pharmacology; Tannins: therapeutic use

Anaphylactic reaction to ingestion of Quercus ilex acorn nut - Vega; DomÍnguez; Cosmes; MartÍnez; BartolomÉ, B; Palacios; Vega, a; Domínguez, C; Cosmes, P; Martínez, a; BartolomÉ, B; Martínez, J; et al. (Clinical & Experimental Allergy, 1998)
Background A patient experienced an anaphylactic reaction after eating acorn nuts, fruit of the holm oak (Quercus ilex), one of the most abundant trees in Spain. Several urticaria episodes upon ingestion of peanuts were also referred. Objective To assess the hypersensitivity reaction to acorn and to characterize the allergenic proteins involved. Methods Cutaneous tests were performed using the skin-prick technique, using a large variety of grass, tree and weed pollens as well as fresh nuts and nut extracts. Specific IgE determination was assessed by RAST. IgE binding bands were determined by SDS-PAGE immunoblotting. Results Skin-prick tests were strongly positive with acorn and peanut. Olea europaea, Quercus alba, Quercus ilex and grass pollens also elicited a weal higher than negative control. Patient serum had measurable levels of IgE antibodies especially to acorn, peanut and grass pollens. Only one protein band, of 17.9 kDa molecular mass, showed IgE-binding properties in the acorn extract. The possible homology of this strong allergenic protein with the group 1 tree pollen allergens was evidenced by the partial inhibition of the western blot with Bet v 1. Conclusions We present a case of anaphylaxis to acorn ingestion as demonstrated by in vivo and in vitro results. A 17.9 kDa IgE-binding band, showing some homology to group 1 pollen tree allergens, was recognized by patient serum.
Keywords: acorn allergens; Anaphylaxis; Anaphylaxis: drug therapy; Anaphylaxis: etiology; Bet v 1; Cross Reactions; Electrophoresis; Food Hypersensitivity; Food Hypersensitivity: drug therapy; Food Hypersensitivity: etiology; Humans; Immunoblotting; Immunoglobulin E; Immunoglobulin E: blood; Male; Middle Aged; nut allergy; Nuts; Nuts: adverse effects; Nuts: immunology; Polyacrylamide Gel; Quercus ilex allergy; Radioallergosorbent Test; Skin Tests

Anaphylactic reaction to ingestion of Quercus ilex acorn nut - Vega; DomÍnguez; Cosmes; MartÍnez; BartolomÉ, B.; Palacios; Vega, a; Domínguez, C.; Cosmes, P.; Martínez, a; BartolomÉ, B.; Martínez, J.; et al. (Clinical & Experimental Allergy, 1998)
Background A patient experienced an anaphylactic reaction after eating acorn nuts, fruit of the holm oak (Quercus ilex), one of the most abundant trees in Spain. Several urticaria episodes upon ingestion of peanuts were also referred. Objective To assess the hypersensitivity reaction to acorn and to characterize the allergenic proteins involved. Methods Cutaneous tests were performed using the skin-prick technique, using a large variety of grass, tree and weed pollens as well as fresh nuts and nut extracts. Specific IgE determination was assessed by RAST. IgE binding bands were determined by SDS-PAGE immunoblotting. Results Skin-prick tests were strongly positive with acorn and peanut. Olea europaea, Quercus alba, Quercus ilex and grass pollens also elicited a weal higher than negative control. Patient serum had measurable levels of IgE antibodies especially to acorn, peanut and grass pollens. Only one protein band, of 17.9 kDa molecular mass, showed IgE-binding properties in the acorn extract. The possible homology of this strong allergenic protein with the group 1 tree pollen allergens was evidenced by the partial inhibition of the western blot with Bet v 1. Conclusions We present a case of anaphylaxis to acorn ingestion as demonstrated by in vivo and in vitro results. A 17.9 kDa IgE-binding band, showing some homology to group 1 pollen tree allergens, was recognized by patient serum.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd, UK accession-num: 9677139
Keywords: acorn allergens; Anaphylaxis; Anaphylaxis: drug therapy; Anaphylaxis: etiology; Bet v 1; Cross Reactions; Electrophoresis; Food Hypersensitivity; Food Hypersensitivity: drug therapy; Food Hypersensitivity: etiology; Humans; Immunoblotting; Immunoglobulin E; Immunoglobulin E: blood; Male; Middle Aged; nut allergy; Nuts; Nuts: adverse effects; Nuts: immunology; Polyacrylamide Gel; Quercus ilex allergy; Radioallergosorbent Test; Skin Tests